Public Relations Strategies and the Marketing Performance of Financial Service Providers - Inyang Bassey Inyang; Glory Sunday Etim; Edim James (Yayasan Ahmar Cendekia Indonesia, 2022)
This study examined public relations strategies and the marketing performance of financial service providers. It aimed to ascertain the influences of community relations, customer relations, social media relations and crisis management on the marketing performance of commercial banks. Cross-sectional survey research design was adopted. Applying a convenience sampling method, primary data were obtained from 175 customers of commercial banks using an adapted 5-point Likert scale questionnaire. The data were analyzed using descriptive statistics, while the hypotheses developed for the study were tested using multiple linear regression. The findings of the study revealed that customer relations (p-value = 0.000 < 0.05) and crisis management (p-value = 0.000 < 0.05) had significant positive effects on the marketing performance of commercial banks, while community relations (t-value = -5.976) and social media relations (t-value = -3.906) had significant negative effects on marketing performance in this regard. On the basis of the findings made, practical implications were presented in the study for possible application by financial service providers.